Răspuns :
...................................................
[tex]\it ax -a =12 \Leftrightarrow a(x-1) =12\Leftrightarrow a =\dfrac{12}{x-1}\ \ \ \ (*) \\\;\\ \\ \it a = 3\ \ \ \ \ (**) \\\;\\ (*), (**) \Rightarrow \it a = \dfrac{12}{3-1} =\ \dfrac{12}{2} \Longrightarrow a =6\ \ .[/tex]
[tex]\it ax -a =12 \Leftrightarrow a(x-1) =12\Leftrightarrow a =\dfrac{12}{x-1}\ \ \ \ (*) \\\;\\ \\ \it a = 3\ \ \ \ \ (**) \\\;\\ (*), (**) \Rightarrow \it a = \dfrac{12}{3-1} =\ \dfrac{12}{2} \Longrightarrow a =6\ \ .[/tex]